Seismic Hazard Assessment in Maluku Province Using PSHA - Setiawan, Yoga; Fathani, Teuku Faisal; Faris, Fikri (Universitas Negeri Yogyakarta, 2023)
On 10 January 2023, a strong earthquake with a moment magnitude (Mw) of 7.5 occurred in Banda Sea, Maluku Province. This earthquake caused casualties around the epicentre due to the building collapse which was not an earthquake-resistant structure. A high level of seismic vulnerability and non-standard infrastructure often result in large losses when earthquakes occur. Therefore, mapping of earthquake-prone areas needs to be carried out to optimize the mitigation efforts based on Peak Ground Acceleration (PGA) and Spectrum Acceleration (SA) values. In this paper, mitigation efforts are carried out by mapping earthquake-prone areas using Probabilistic Seismic Hazard Analysis (PSHA) which considers the potential of each complex earthquake source in Maluku Province. Input data was obtained from several earthquake catalogues such as Advanced National Seismic System (ANSS), International Seismological Center (ISC), and United States Geological Survey (USGS) which were processed and analyzed using the Matlab, ZMap, and R-CRISIS programs and mapped using the ArcMap program. The results of PSHA show that Maluku Province is a region with varying levels of earthquake vulnerability. The research results show that the distribution hazard value on PGA in Maluku Province reaches 0.02g to 0.48g for a return period of 500 years and 0.04g to 0.79g for a return period of 2,500 years and on SA for periods of 0.20 seconds and 1.00 second reaches 0.04g to 0.89g and 0.01g to 0.22g for a return period of 500 years and 0.07g to 1.48g and 0.02g to 0.35g for a return period of 2,500 years, respectively. The highest level of vulnerability is in the northern region including Seram Island, Way Apu Island and Ambon Island and the lowest level of vulnerability is in the eastern region including Aru Island.